2019
DOI: 10.3390/molecules24173064
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Feruloylserotonin in LPS-Induced HaCaT Cells

Abstract: Epidermal inflammation is caused by various bacterial infectious diseases that impair the skin health. Feruloylserotonin (FS) belongs to the hydroxycinnamic acid amides of serotonin, which mainly exists in safflower seeds and has been proven to have anti-inflammatory and antioxidant activities. Human epidermis mainly comprises keratinocytes whose inflammation causes skin problems. This study investigated the protective effects of FS on the keratinocyte with lipopolysaccharides (LPS)-induced human HaCaT cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Therefore, inflammation of keratinocytes is associated with many skin problems. 2 Although inflammation is a prerequisite for healing, in the case of wounds and in general for skin restoration, uncontrolled inflammation can lead to tissue/skin damage and injuries. Consequently, alleviation of inflammatory injury is a pivotal step in the prevention of skin/tissue injury progression.…”
mentioning
confidence: 99%
“…Therefore, inflammation of keratinocytes is associated with many skin problems. 2 Although inflammation is a prerequisite for healing, in the case of wounds and in general for skin restoration, uncontrolled inflammation can lead to tissue/skin damage and injuries. Consequently, alleviation of inflammatory injury is a pivotal step in the prevention of skin/tissue injury progression.…”
mentioning
confidence: 99%
“…Apart from oxidative damage occurring with diabetic wounds, bacterial infection is another major cause that hinders the re-epithelization process (He et al 2019 ). Accordingly, it was decided to investigate whether CoPP pretreatment could enhance the motility of HaCaT while culturing the cells in HG media containing lipopolysaacharide (LPS).…”
Section: Resultsmentioning
confidence: 99%
“…In LPS-stimulated cell lines, nuclear factor kappa B (NF-κB) is an important transcription factor in the expression of iNOS and COX-2 genes [ 33 , 34 ]. In LPS-induced human keratinocyte HaCaT cells, He et al [ 35 ] found that feruloylserotonin suppressed the toll-like receptor (TLR4)/NF-κB pathway and promoted the translocation of Nuclear factor-erythroid 2 related factor 2 (Nrf2). The chloroform fraction of Carpinus tschonoskii inhibited the protein and mRNA of chemokine in HaCaT cells by downregulating STAT1 in the IFN-γ signaling pathway [ 36 ].…”
Section: Resultsmentioning
confidence: 99%